Brain metabolite levels and language abilities in preschool children. Issue 10 (11th August 2016) - Lebel, Catherine; MacMaster, Frank P.; Dewey, Deborah
Abstract: Introduction: Language acquisition occurs rapidly during early childhood and lays the foundation for future reading success. However, little is known about the brain–language relationships in young children. The goal of this study was to investigate relationships between brain metabolites and prereading language abilities in healthy preschool‐aged children. Methods: Participants were 67 healthy children aged 3.0–5.4 years scanned on a 3T GE MR750w MRI scanner using short echo proton spectroscopy with a voxel placed in the anterior cingulate gyrus ( n = 56) and/or near the left angular gyrus ( n = 45). Children completed the NEPSY‐II Phonological Processing and Speeded Naming subtests at the same time as their MRI scan. We calculated glutamate, glutamine, creatine/phosphocreatine, choline, inositol, and NAA concentrations, and correlated these with language skills. Results: In the anterior cingulate, Phonological Processing Scaled Scores were significantly correlated with glutamate, creatine, and inositol concentrations. In the left angular gyrus, Speeded Naming Combined Scaled Scores showed trend correlations with choline and glutamine concentrations. Conclusions: For the first time, we demonstrate relationships between brain metabolites and prereading language abilities in young children. Our results show relationships between language and inositol and glutamate that may reflect glial differences underlying language function, and a relationship of language with creatine. The trend between Speeded Naming and choline is consistent with previous research in older children and adults; however, larger sample sizes are needed to confirm whether this relationship is indeed significant in young children. These findings help understand the brain basis of language, and may ultimately lead to earlier and more effective interventions for reading disabilities. Abstract : Language skills in preschool predict later reading ability, but the relationship between language and brain metabolites in young children is unknown. In this study, we find that brain metabolites are associated with language abilities in children before reading begins. We show glutamate–language relationships consistent with previous studies, and present novel data showing creatine–language and inositol–language relationships that may be unique to preschool children.